A Preliminary Cross-sectional Survey Study to Determine the Prevalence of Internet Addiction in Postgraduate Scholars of National Institute of Ayurveda, Jaipur - Tina Gorisariya; Sudipta Kumar Rath (Journal of Ayurveda)
Introduction: The advent of the Internet has revolutionized society, making the world more accessible. With such widespread use, Internet addiction (IA) is emerging as a significant concern, especially among university students who rely heavily on the Internet academic and personal purposes. The objective of this study is to assess the prevalence of IA using Young’s IA Test (IAT) among postgraduate scholars at National Institute of Ayurveda, Jaipur and to identify demographic factors associated with IA. Methods: A cross-sectional survey was conducted from January 20, 2025, to January 30, 2025, using a structured questionnaire sent via Google Forms. The survey included demographic details and the IAT questionnaire. The IAT is a validated 20-item scale measuring the severity of Internet dependency. Results: Out of 194 responses, 189 valid responses were analyzed. The mean age of participants was 29.3 ± 5.1 years. Approximately 72% were female, and 28% were male. The majority were from the Dravyaguna department (23%), and the Panchkarma department had the least respondents (1.5%). The highest number of respondents was from the academic year 2024 to 2025 (36%). About 40% of participants exhibited mild IA, with younger age groups (23–32 years) and males showing a higher prevalence. Conclusion: The study found a significant portion of the sample population experiencing mild IA. Younger students and males are more prone to IA, indicating reliance on the Internet for academic and social purposes. The high prevalence underscores the need for awareness programs, counseling services, and monitoring strategies to promote healthy Internet usage.